Pemberdayaan Pedagang Pasar dengan Pemanfaatan Aplikasi Online Menuju Digitalisasi Pasar Rakyat di Kabupaten Bantul - Purwani, Diah Ajeng; Pratiwi, Fatma Dian; Puspitasari, Niken; Virga, Rika Lusri; Nusa, Lukman (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
The pandemic problem seems to have forced all economic sectors to recover, including market traders, community groups who are under pressure because of this phenomenon. The omzet that has been obtained so far is difficult to return to before the pandemic due to changes towards new normal. This research is based on the Community Based Research method on groups of people's market traders in Bantul Regency. The study found that traders experienced difficulties in adjusting to themselves due to a lack of information technology proficiency. The solution to the problem starts with optimizing the most familiar social media to merchants, namely Whatsapp. The use of WhatsApp Business is used to promote the products. Optimizing Whatsapp business provides a new strategy for conducting marketing promotions. The optimization through exploring product photos technique and persuasive message through captions. In the end, the market traders start getting new customers by uploading stories and uploading products.